Visualisasi Apendiks pada USG Abdomen di RS Kasih Ibu Saba, Gianyar, Indonesia: Hasil Penelitian - Made Alit Darmawan; I Komang Artawan (Cermin Dunia Kedokteran, 2024)
Appendicitis is the frequent cause of right lower abdominal pain. Ultrasound is the first modality for diagnosis, with sensitivity, specificity, positive predictive rates, and predictive rates were 86%, 94%, 100%, and 92%. This modality has high accuracy and no radiation side effects. However, the sensitivity and specificity of this examination vary due to several factors such as the operator, equipment, or patient condition. This study aims to determine the average distance of appendix from abdominal wall that can be visualized by ultrasound. From 103 patients with right lower abdominal pain, 32.05% appendix can be visualized and 53.12% patients diagnosed with appendicitis. The average distance of appendix from abdominal wall which can be visualized by ultrasound is 22.828 mm.